The periplasmic protein HslJ is the first-line of defense against oxidative stress in Acinetobacter baumannii - Daniela Scribano; Martina Pasqua; Dolores Limongi; Lucia Nencioni; Anna Teresa Palamara; Cecilia Ambrosi (Biological Research)
Abstract Background Acinetobacter baumannii poses a significant threat globally, causing infections primarily in healthcare settings, with high mortality rates. Its adaptability to antibiotic resistance and tolerance to various stresses, including reactive oxygen species (ROS), contribute to its persistence in healthcare environments. Previous evidence suggested that the periplasmic heat shock protein, HslJ-like protein (ABUW_2868), could be involved in oxidative stress defense in A. baumannii. In this study, we demonstrate the pivotal function of HslJ as the first line of defense against oxidative damage induced by hydrogen peroxide (H2O2). Methods An isogenic site-specific hslJ mutant of A. baumannii AB5075 was used to evaluate its sensitivity to H2O2, survival rate in human macrophages, biofilm, cell surface hydrophobicity, and motility. Additionally, the hslJ expression profile was measured under stress conditions and its OxyR-dependent regulation was assessed both in vitro and in a heterologous host. Results Herein, we report that HslJ is under the positive regulatory control of OxyR, which upregulates its expression in response to imipenem (IMP) and H2O2, thereby underscoring its importance in A. baumannii survival strategy. In addition, our findings revealed that the hslJ mutant displayed abrogated surface-associated motility accompanied by increased cell surface hydrophobicity (CSH), indicating also a role in maintaining cell membrane properties. Conclusions This comprehensive understanding of HslJ multifaceted role not only enriches our knowledge of A. baumannii stress response mechanisms but also provides valuable insights for developing targeted strategies to eradicate this deadly resilient pathogen in healthcare settings.